2019
DOI: 10.3389/fphar.2019.00979
|View full text |Cite
|
Sign up to set email alerts
|

ITRAQ-Based Proteomics Analysis Reveals the Effect of Neoliensinine on KCl-Induced Vascular Smooth Muscle Contraction by Inhibiting Regulatory Light Chain Phosphorylation

Abstract: Smooth muscle (SM) contraction is one of the important physiological functions of the human body, and SM abnormal contraction will induce many diseases. The phosphorylated regulatory light chains (p-RLC) play a decisive role in SM contraction, and dephosphorylation of p-RLC is an effective way to relax SM. Our previous study showed that the novel benzylisoquinoline alkaloid, neoliensinine (Neo), could relax microvascular SM contracted by KCl hyperpolarization. In this study, mesenteric capillaries isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…In addition to the hyperproliferation of PASMCs, hypoxia-induced contraction of PASMCs is also one of the crucial factors leading to PH 32 . Recently study found that neoliensinine, a novel benzylisoquinoline alkaloid extracted from Plumula Nelumbinis, has the effect of relaxing vascular smooth muscle cells 33 . The above study results show that the anti-PH effect of Plumula Nelumbinis may also be related to the inhibition of excessive contraction of PASMCs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the hyperproliferation of PASMCs, hypoxia-induced contraction of PASMCs is also one of the crucial factors leading to PH 32 . Recently study found that neoliensinine, a novel benzylisoquinoline alkaloid extracted from Plumula Nelumbinis, has the effect of relaxing vascular smooth muscle cells 33 . The above study results show that the anti-PH effect of Plumula Nelumbinis may also be related to the inhibition of excessive contraction of PASMCs.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that the vascular smooth muscle contraction pathway may play an essential role in the occurrence and progression of CHF. The vascular smooth muscle contraction pathway mediates hypertension, portal hypertension, and vascular endothelial injury (17,18). These pathological changes increase the risk of CHF to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…, in vitro cell experiments demonstrated that alkaloid rich fractions of lotus and neferine have potent inhibitory effects on vascular smooth muscle cell (VSMC) proliferation and migration by abolishing PDGF-Rb activation, dephosphorylation of extracellular signal-regulated kinase (ERK)1/2, inactivation of JNK/P38 MAPK, and downregulation of fractalkine gene expression(Jun et al 2016;Li, Tong, et al 2010;Zheng et al 2014). Through iTRAQ proteomics analysis, blocking phospholipase Cβ (PLCβ) and 145 multidomain guanine nucleotide exchange factor 12 (RhoGEF12) expression by activation of G protein-coupled receptor (GPCR) signaling may be responsible for neoliensinine-dependent vascular smooth muscle relaxation(Yang,Yan et al 2019). The protective effect of neferine (10 μM) on H9c2 cardiomyoblasts was demonstrated by reduced doxorubicin-induced apoptosis mediated by the regulation of the NADPH oxidase/ROS-mediated NF-κB redox and insulin-like growth factor (IGF)/Nrf2 signalling pathways(Bharathi Priya et al 2018;Priya et al 2017).…”
mentioning
confidence: 99%